Using Data Mining to Predict Possible Future Depression Cases - Kevin Daimi; Shadi Banitaan (International Journal of Public Health Science (IJPHS), 2014)
Depression is a disorder characterized by misery and gloominess felt over a period of time. Some symptoms of depression overlap with somatic illnesses implying considerable difficulty in diagnosing it. This paper contributes to its diagnosis through the application of data mining, namely classification, to predict patients who will most likely develop depression or are currently suffering from depression. Synthetic data is used for this study. To acquire the results, the popular suite of machine learning software, WEKA, is used.